Corrupted cultures in mental health inpatient settings. Is restraint reduction the answer? - PATERSON, B.; MCINTOSH, I.; WILKINSON, D.; MCCOMISH, S.; SMITH, I. (Journal of Psychiatric & Mental Health Nursing (John Wiley & Sons, Inc.), 2013)
Accessible summary Restraint in mental health is a sensitive area of practice., If permitted, restraint in mental health seems to have a tendency to be used excessively., We need to understand better why this tends to happen in order to prevent it., Abstract The early years of the 21st century have seen successful efforts in a number of countries to reduce the use of restraint in services for people with mental health problems. An underlying emphasis on 'cultural change' is characteristic of such initiatives reflecting, it appears, the re-emergence of interest in the therapeutic milieu. Such efforts have though lacked a comprehensive explanation of how organizational culture plays a role in the development of the excessive use of restraint, which seems to respond to such initiatives. This paper seeks to address that deficit and draws in particular on the concepts of corrupted culture, institutional violence, trauma, parallel processing and contemporary research on restraint and seclusion reduction. In doing so it examines whether restraint reduction initiatives represent part of the solution to the problem of corruption, which is intrinsically associated with the legitimatization of coercion.